Parent Guidance Pattern in Growing Children's Independence - Dafetta Fitri Linda; MHD Natsir (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
The objective of the present study describes the importance of parental guidance in fostering children's independence. Indicators of children's independence that are grown by parents in this study are self-confidence, discipline and positive habits. This research is a qualitative research with naturalistic phenomenology approach. The subjects of the study were parents of children who studied in Play Group Harapan, Pekanbaru. In collecting the data, observation, interview and documentation were administered. This study used an interactive analysis model of Miles and Huberman which consist of data reduction, data presentation and concluding conclusions. The results of the study show that there were three patterns of guidance that parents do to foster children's independence. Firstly, fostering self-confidence by accompanying children in their activities, patiently guiding children, familiarizing children according to their abilities. Secondly, shaping the disciplined attitude of the child who is responsible for his toys, accustoms the time spent in daily activities, makes good communication. Third, develop positive habits in children by making parents as role models for children, always keeping promises, giving words of praise, getting used to being involved in various activities.Keywords: Discipline, Guidance Pattern, Independent, Self-Confidence